Thioredoxin-interacting protein mediates dysfunction of tubular autophagy in diabetic kidneys through inhibiting autophagic flux - Huang, Chunling; Lin, Mike Z; Cheng, Delfine; Braet, Filip; Pollock, Carol A; Chen, Xin-Ming (Laboratory investigation, 2014)
Thioredoxin-interacting protein (TXNIP) expression is ubiquitous and is induced by a variety of cellular stresses, including high intracellular glucose. TXNIP is associated with activation of oxidative stress and tubulointerstitial fibrosis in diabetic nephropathy. Autophagy is a major pathway that delivers damaged proteins and organelles to lysosomes to maintain cellular homeostasis. This study aimed to investigate the dysregulation of autophagy and the regulation of TXNIP on autophagy in renal proximal tubular cells (PTCs) under diabetic conditions. The formation of autophagosomes was measured using transmission electron microscopy, and LC3-II, and the effectiveness of autophagic clearance was determined by p62 expression in diabetic kidney and in human PTCs exposed to high glucose (HG). The results collectively demonstrated increased expression of TXNIP, LC3/LC3-II and p62 in renal tubular cells of mice with diabetic nephropathy and in cultured human PTCs exposed to HG (30 mM/l) for 48 h compared with control. The formation of autophagic vacuoles was increased in HG-induced cells. Furthermore, silencing of TXNIP by siRNA transfection reduced autophagic vacuoles and the expression of LC3-II and p62 in human PTCs exposed to HG compared with control and partially reversed the accumulation of LC3-II and p62 induced by bafilomycin A1 (50 nM/l), a pharmacological inhibitor of autophagy which blocks the fusion of autophagosomes with lysosomes and impairs the degradation of LC3-II and p62. Collectively, these results suggest that hyperglycemia leads to dysfunction of autophagy in renal tubular cells and decreases autophagic clearance. HG-induced overexpression of TXNIP may contribute to the dysfunction of tubular autophagy in diabetes.